Analisis Tarif Air PDAM Untuk Kelayakan Penerapan Sistem Pemanenan Air Hujan pada Skala Rumah Tangga: Drinking Water Tariff Analysis For The Feasibility of Implementing Rainwater Harvesting Systems at The Household Scale - Juliana, Imroatul Chalimah; Taufik Ari Gunawan; Siti Aisyah Nurjannah; Eric Ho (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
The limited availability of clean water is a problem that often occurs lately. Water use continues to increase due to population growth and technological developments. The availability of abundant rainwater and the application of a rainwater harvesting system are alternatives for water fulfillment as water supplies are limited. Rainwater harvesting system performance simulation modeling is essential in deciding the suitability of rainwater harvesting systems. In this study, the rainwater harvesting system simulation modeling was carried out using the Yield Before Spillage (YBS) algorithm in 3 cities in Indonesia (Palembang City, Bogor City, and Mataram City). This assessment considers 5 combinations of demand, 5 combinations of catchment area, 5 tank capacities, and 3 applicable water rates, resulting in 1,875 different value configurations. The performance and potential assessment of the rainwater harvesting system are determined by Water Saving Efficiency and Timetric Reliability, while the financial assessment is determined using the payback period and benefit-cost ratio. Benefits are derived from the potential for water savings with a rainwater harvesting system which is converted into financial savings according to the prevailing water rates and costs are determined based on the initial installation costs of the rainwater harvesting system. The results of this study indicate that the city of Bogor with an average rainfall of 3805.95 mm/year has the highest WSE rate of 100% and the fastest payback period is 4 years. Palembang City with an average rainfall of 2551.57 mm has the highest WSE rate of 99,273% and the fastest payback period is 5.42 years. Mataram, with an average rainfall of 1661.79 mm, has the highest WSE rate of 91.752% and the fastest payback period is 8.17 years. Topographical conditions and rainfall greatly affect the performance of the rainwater harvesting system.